The Influence of Discovery Learning Model on Student Activeness and Sociology Learning Outcomes - Nihla Mar'atus Sholihah; Saiful Amin (SAINTIS Publishing, 2025)
The problem identified is the limited involvement and learning outcomes of student learning, which is caused by a lack of diverse and student -centered teaching methods. Therefore, the application of innovative and interactive learning models such as discovery learning is very important to increase student involvement and understanding. The main objective of this study is to evaluate how the discovery learning model affects the involvement of students of class XI IPS Sociology MA Bilingual Batu. Identifying the effect of learning models on the learning outcomes of class XI IPS Sociology in MA Bilingual Batu is the second goal. This study uses quantitative methods based on quasi-experimental design using the structure of non-Ekuivalent control groups. The data collection process involves the granting of the active questionnaire together with the pretest and posttest assessment to measure student learning outcomes. The data produced underwent a series of analyzes, including normality tests, homogeneity tests, N-Gain tests, and independent sample t-tests. The results showed that the application of the discovery learning model had a significant impact on increasing student activity. Discovery learning also significantly affects student learning outcomes. For further research, it is recommended to examine other more diverse variables that can affect the effectiveness of the discovery learning model, using the latest theories so that the findings produced are more relevant to the times. In addition, research can expand its scope by including various levels of education and different subjects to determine how wide the discovery learning model can be used effectively.